(untitled) (مجلة إحالات, 2026)
This research seeks to highlight the efforts of a prominent Algerian scholar in the field of bibliographic authorship. This is related to Prof. Dr. Mokhtar Bouanani, who made abundant contributions in this field of knowledge. In order to introduce the reader - general or specialist - to his most important bibliographic works, to determine their cognitive value, to clarify their methodological importance on the one hand, and to reveal some features of the bibliographic industry used in developing these works on the other hand.